Cover Image. Issue 10 (21st April 2021) - Soret, Pierre‐Antoine; Lam, Laurent; Carrat, Fabrice; Smets, Lena; Berg, Thomas; Carbone, Marco; Invernizzi, Pietro; Leroy, Vincent; Trivedi, Palak; Cazzagon, Nora; Weiler‐Normann, Christina; Alric, Laurent; et al.
Abstract : The cover image is based on the Original Article Combination of fibrates with obeticholic acid is able to normalise biochemical liver tests in patients with difficult‐to‐treat primary biliary cholangitis by Pierre‐Antoine Soret et al., https://doi.org/10.1111/apt.16336